Compensation for Moral Harm in Foreign Law and Order - Tabunshikov, Andrey T.; Akhmedov, Ruslan M.; Stepanov, Dmitry V.; Ivanova, Yuliya A.; Marukhno, Vasilisa M. (Opción, 1970)
The authors of the paper conducted a comparative law research of the current civil legislation governing compensation for moral harm in foreign countries. The article defines the basic terms used in foreign law which are analogues of the institute of “compensation for moral harm” existing in Russia and neighboring countries